Innovative Approaches to Wastewater Treatment Using Bioengineering Techniques - Dr. Tasneem K. H. Khan; Dr. V. Gurumurthy; Mr. V. Rajasekhar Reddy; Dr Ajay Kumar Verma; Dr. Sanjay Kumar Singh; M. Aneez Mohamed; Dr. Sneha Khadse (The Bioscan, 2025)
In the recent past, effluent disposal has become one of the greatest concerns in the world because of increase industrialization and urbanization resulting to water pollution. This has facilitated the attempt at looking at diseases in a new light and therefore coming up with a new paradigm shift on treating diseases or diversification of the approach by overcoming environmental, economical or social barriers to diseases and treatment through out of the box thinking. Therefore, bioengineering, a branch of biology and engineering sciences, is regarded as one of the most suitable solutions to the problems of wastewater treatment. The function of microorganisms, plants as well as bioengineering activities such as bioreactors, bio augmentation and phytoremediation on wastewater is discussed in this paper. It explores stet opportunities that can be exploited in the removal of pollutants and the potential for getting valuable resources back in the form of microbial technologies, constructed wetlands and NMIs. In addition, there are modern materials like nanomaterials, microbial electrochemical system, and membrane bioreactor for wastewater treatment included in the subject. From this paper, it is concluded that bioengineering is about enhancing the mechanism of wastewater treatment through sustainable approaches and the circular economy.